2013
DOI: 10.1080/09540121.2012.729803
|View full text |Cite
|
Sign up to set email alerts
|

Reducing cultural and psychological barriers to Latino enrollment in HIV-prevention counseling: Initial data on an enrollment meta-intervention

Abstract: Aspects of Latino culture (e.g., machismo, marianism) can act as barriers to enrollment in HIV-prevention programs. To lift these barriers, a culturally appropriate meta-intervention was designed to increase intentions to enroll in HIV-prevention counseling by Latinos. Latino participants (N = 41) were recruited from the community and randomly assigned to either an experimental or control meta-intervention condition that varied the introduction to a HIV-prevention counseling program. Following the meta-interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Additionally, prior work has shown that the mean age of participants enrolling in HIV-prevention intervention programs falls within this range (e.g., Durantini, & Albarracín, 2012; Liu et al, 2014; Wilson, Durantini, Albarracín, Crause & Albarracín, 2013). Despite this age range restriction, we do not believe the generalizability of the studies should be affected, as the meta-interventions used target broad psychological themes, such as seeking self-validation or maximizing objective outcomes, which are not limited to specific age groups.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, prior work has shown that the mean age of participants enrolling in HIV-prevention intervention programs falls within this range (e.g., Durantini, & Albarracín, 2012; Liu et al, 2014; Wilson, Durantini, Albarracín, Crause & Albarracín, 2013). Despite this age range restriction, we do not believe the generalizability of the studies should be affected, as the meta-interventions used target broad psychological themes, such as seeking self-validation or maximizing objective outcomes, which are not limited to specific age groups.…”
Section: Discussionmentioning
confidence: 98%
“…Studies on a range of health outcomes have emphasized the importance of culturally competent services [44]. Health interventions that take culture into account, which include nativity, have been found effective in addressing various health outcomes such as smoking [45], HIV prevention [46], and weight loss [47]. Few intervention or health service studies exist that focus on Latino criminal justice clients.…”
Section: Introductionmentioning
confidence: 99%
“…While homophobia and stigma related factors are a challenge for any group in HIV prevention, these challenges are particularly highlighted among Hispanics because of noted cultural concepts that reinforce common barriers to effective HIV prevention. Furthermore, machismo may lead to reluctance of utilizing services as Hispanic men are often reluctant to participate in activities, especially health promotional ones that may challenge their pride or do not reinforce their masculinity (Wilson et al, 2012). If infected with HIV, Hispanic individuals often avoid seeking testing, counseling, or treatment because of the discrimination and shame present, linked to the stigma associated with HIV.…”
Section: Despite Widespread Awareness Of the Overrepresentation Of Himentioning
confidence: 99%
“…Marianismo is a term used to identify another gender specific cultural idea that women should be sexually pure and non-confrontational in Hispanic communities (Wilson et al, 2012). This may contribute to the fears of stigma surrounding a woman being viewed as "easy" or may leave a woman disempowered to get tested or ask her partner to do so.…”
Section: Despite Widespread Awareness Of the Overrepresentation Of Himentioning
confidence: 99%
See 1 more Smart Citation